Perekayasaan Akuntansi Istishna’ Pada Produk Pembiayaan Apartemen - Erina Maulidha; Asrul Aminulloh (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2013)
Adoption of PSAK 104 on Accounting Istishna, creating an obstacle for Islamic banks.Plus the difficulty of implementing the contract istishna itself in the banking business.PSAK related more appropriately applied to the real sector companies engaged insteadof banking services. This study aims to determine the constraints and associated engineering analysis accounting istishna ‘apartment on financial products in Islamic banks.The research method used is descriptive qualitative field research. Analysis was used tocompare the conditions obtained in the field by the recognition of regulated accountingunder PSAK 104 and the legislation in force. Based on the analysis, there are severalobstacles that arise in the application of financing istishna, which is related to information technology, human resources and the prevalence of apartment construction businessin Indonesia in the implementation of accounting standards. Consequently, in practice,Islamic banks have not fully adopted PSAK 104, especially in terms of disbursement offunds to the developer, the recognition of revenue on accrual basis and cash basis, andmargin recognition in installments during construction by the customer.